Living unspecified kidney donation around the world: Gaps and best practice - Kurleto, Paulina; Skorupska-Król, Agnieszka; Bramstedt, Katrina Andrea (Nursing in the 21st Century, 2022)
LIVING UNSPECIFIED KIDNEY DONATION AROUND THE WORLD: GAPS AND BEST PRACTICE Introduction. Kidney transplantation is the preferred form of treatment for patients with end-stage renal disease (compared to dialysis). Many countries allow living donor kidney transplantation to address organ shortage from deceased donors. There are several types of donation depending on the relationship of the living donor to the recipient. The Ethics, Legal and Psychosocial Aspects of Organ Transplantation (ELPAT) section of the European Society for Organ Transplantation (ESOT) classifi es altruistic kidney donation to a stranger as “unspecifi ed”. Unspecifi ed living donation is not a new form of donation, but it is only legal in a small number of countries. Aim. The aim of the study is to compare the practice of live unspecifi ed kidney donation in the world. This article summarizes the knowledge of the prevalence of unspecifi ed kidney donation, the donor candidate evaluation process, perioperative donor support, and the ethical dilemmas that accompany this procedure.